PENGARUH EDUKASI MEDIA BOOKLET TERHADAP PENGETAHUAN KELUARGA TENTANG DETEKSI DINI STROKE - siti romadoni (IKesT Muhammadiyah Palembang, 2023)
ABSTRACT Background: Stroke is a health problem that needs attention because stroke is the number one cause of death in the world (200 per 100,000 population in one year) and the highest cause of death in Indonesia (500,000 people with 125,000 deaths and the rest are disabled), caused by delays instroke treatment in the prehospital phase (83,9%) due to a lack of knowledge in the community, especially families, about early detection of strike. Steps that can be taken to increase knowledge include conducting education using booklet media. A booklet is a medium that can be used to convey information in the form of a book containing writing and pictures. Purpose: To determine the effect of education using booklet media on family knowledge about early stroke detection. Method: This type of quantitative research uses Pre-experimental design with the One-Group Pretest-Postest design approach. Sampling used a purposive sampling technique of 59 respondents, namely families with a high risk of stroke in the working area of the Nagaswidak Health Center. The study used an instrument of knowledge about early stroke detection with as many as 20 questions that had been tested for validity and reliability at the Pembiuna Palembang Health Center. The data obtained were analyzed using the Wilcoxon test. Results: The results of the analysis on the knowledge variable obtained showed that the value of knowledge before education was a median of 11 with a minimum value of 0 and a maximum value of 18, and the value of knowledge after educationwas median of 15 with a minimum value of 8 and a maximum value of 20. The results of the data analysis with the Wilcoxon test obtained a p-value of 0.000 (<0.05). Conclusion: there is an effect of health education using booklet media on family knowledge about early stroke detection. Suggestions for future researchers to be able to carry out further research that focuses on the ability of families to carry out early detection of stroke with the demonstration method. Keyword: Education, Early Stroke Detection, Booklet Media, Knowledge